Sustainability at Crossroads: The Conflicting Needs of Affordable Housing Development Versus Saltpan Conservation in Mumbai, India - Sujayita Bhattacharjee; Sanjukta Sattar (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Housing in Mumbai has emerged as a contentious issue, sparking the urban growth debate, with recent attention on Mumbai's saltpans earmarked for development. This study explores the aspect of sustainability amidst the conflicting needs of affordable housing development and salt pan conservation. It aims to evaluate the sustainability challenges and trade-offs between affordable housing development and salt pan conservation in Mumbai. The study uses data reviewed from a variety of journals, news articles, books, websites, etc., and by using these employs a PESTEL (Political, Economic, Social, Technological, Environmental, and Legal) analysis to delve into the issue. Results show that the conversion of the salt pans into housing zones will potentially undermine their critical ecosystem functions while failing to achieve critical sustainable development goals. Recommendations include prioritising ecologically sensitive urban planning, alternative sites such as brownfield developments, the use of derelict buildings, etc.